Biomechanics of trees: growth, anatomy and morphology - Vargas-Silva, Gustavo (Instituto de Ecología, A.C., 2019)
Trees are the largest and heaviest living beings that have ever lived on Earth. In order to achieve this, trees have wood, an exceptional structural material, and they offer several design strategies. This work is a review of the state of the art related to the strategies of growth, anatomy and morphology that use trees, highlighting general concepts related to structural aspects related to plant biomechanics. Moreover, this paper emphasizes the features of natural plant materials, which have a hierarchical organization, and in most cases are fiber-reinforced composite materials, materials with cellular structure, or both, such as wood.